Agatha Christie's Miss Marple. Set two, volume two. Murder at the vicarage. Nemesis. [videorecording (DVD)] - Christie, Agatha, 1890-1976; Hickson, Joan, 1906-1998; Gallaccio, George (Miss Marple., 1986)
Work 1. When Colonel Lucius Protheroe; the most hated man in the village of St. Mary Mead, is found dead there is no shortage of suspects. Work 2. Miss Marple is asked to solve a crime and right an injustice; there's just one problem, first she must discover what crime was committed.